2019
DOI: 10.1007/s40291-019-00382-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of all Four Gardnerella vaginalis Clades Detects Abnormal Vaginal Microbiota Characteristic of Bacterial Vaginosis More Accurately than Putative G. vaginalis Sialidase A Gene Count

Abstract: Background Bacterial vaginosis (BV) is a vaginal disorder characterized by a depletion of the normal lactobacillus-dominant microbiota and overgrowth of mainly anaerobic bacteria. Objectives The study aimed to evaluate the distribution and abundance of the Gardnerella vaginalis clades and sialidase A gene in vaginal samples from Russian women, and investigate if the G. vaginalis sialidase A gene count detects an abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 44 publications
8
36
1
1
Order By: Relevance
“…The relationship between Gardnerella abundance and Nugent score is not surprising, as the presence of Gardnerella "morphotypes" on Gram-stained slides of vaginal specimens is part of the calculation of the clinical score (3). The lack of association of G. leopoldii with Nugent category is interesting in that this species was previously investigated together with G. swidsinskii as cpn60 subgroup A/clade 4, which was found to be associated with Nugent category (14,23,31). These species are very closely related phylogenetically ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between Gardnerella abundance and Nugent score is not surprising, as the presence of Gardnerella "morphotypes" on Gram-stained slides of vaginal specimens is part of the calculation of the clinical score (3). The lack of association of G. leopoldii with Nugent category is interesting in that this species was previously investigated together with G. swidsinskii as cpn60 subgroup A/clade 4, which was found to be associated with Nugent category (14,23,31). These species are very closely related phylogenetically ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a sexually transmitted infectious agent, TV is found to cause local inflammation, and it affects the clearance of hr-HPV and contributes to cervical lesion detection in several research, but it is controversial [8]. Some studies have demonstrated a correlation between vaginal infection and the carcinogenicity of hr-HPV, but most of them are small-scale researches, and their conclusions are inconsistent [5,[9][10][11][12][13][14][15][16]. This research is with the most massive scale and the most comprehensive investigation about the correlation between cervical hr-HPV infection, CIN/ ICC, and the vaginal microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between Gardnerella abundance and Nugent score is not surprising, as the presence of Gardnerella “morphotypes” on Gram stained slides of vaginal specimens is part of the calculation of the clinical score [3]. The lack of association of G. leopoldii with Nugent category is interesting in that this species was previously investigated together with G. swidsinskii as cpn60 subgroup A/clade 4 which was found to be associated with Nugent category [14, 34, 40]. These species are very closely related phylogenetically (Figure 1), and were only resolved by Vaneechoutte et al [13] by MALDI-TOF and whole genome comparison, so the specific factors responsible for their apparently different relationships with the microbiological definition of BV remain to be identified.…”
Section: Resultsmentioning
confidence: 99%